Oral impact on daily performance (OIDP) scale for use in Sri Lankan adolescents: a cross sectional modification and validation study - Uttara Amilani; Prasanna Jayasekara; Irosha R. Perera; Hannah E. Carter; Sameera Senanayake; Sanjeewa Kularatna (BMC, 2020)
Abstract Background Oral Health Related Quality of Life (OHRQoL) measures play an important role in understanding subjective patient experiences in oral health care. The Oral Impact on Daily Performance (OIDP) scale is a validated OHRQoL tool that measures the impact and extent to which an individual's daily activities may be compromised by their oral health. It is commonly used to facilitate oral health service planning. The aim of this study was to modify and validate a Sinhalese version of the OIDP for use in Sri Lankan adolescents. Methods Stage I involved cultural adaptation of the tool through translation and modification. Stage II involved the exploring factor structure, validation and a reliability assessment. After translation and cultural adaptation, stage II was conducted among 220 secondary school students aged 15-19 in the Gampaha district, Sri Lanka. Participants completed the modified OIDP scale along with questions on self-reported perceived oral health problems and treatment need which were used to assesses the concurrent validity of the modified OIDP scale. Factorability was assessed by inspection of correlation matrix and Kaiser-Meyer-Olkin and Bartlett's Test of Sphericity tests as a measure of sampling adequacy. An exploratory factor analysis was carried out using Principal Component Analysis method and factors were rotated using the oblimin method. Results The Kaiser-Meyer-Olkin measure was 0.87 and Bartlett's test of Sphericity was significant (p < 0.001) Cronbach's alpha was calculated as 0.88, indicating a high level of internal consistency of the modified OIDP scale. The principal component analysis produced two factors with Eigen values ranging from 1.12 to 4.40, explaining 70.0% of total variance. Concurrent validity was satisfactory as the OIDP score increased when the adolescents' perceived oral health decreased. The final modified OIDP consists of eight self-reported items which assesses the impact severity of eight daily performances over past three months. Participant scores ranged from 0 to 24 out of a worst possible score of 40, and nearly 48% of the responders reported at least one impact during past three months. The most prevalent oral health impact related to chewing and enjoying foods, reported by 36.8% of respondents. Conclusion This study suggests that the modified OIDP scale has promising psychometric properties and is appropriate for use among adolescents in Sri Lanka. Further research is required to test the validity of this tool in other cohorts.